Azacitidine for the treatment of patients with relapsed acute myeloid leukemia after allogeneic stem cell transplantation. Issue 12 (15th October 2021) - Yoshimoto, Goichi; Mori, Yasuo; Kato, Koji; Odawara, Jun; Kuriyama, Takuro; Ueno, Toshiyuki; Obara, Teppei; Yurino, Ayano; Yoshida, Shuro; Ogawa, Ryosuke; Ohno, Yuju; Iwasaki, Hiromi; et al.
Abstract: We retrospectively analyzed 38 patients with AML who received azacitidine (AZA) to treat disease relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Patients with objective response (OR) ( n = 20) after AZA had significantly higher 2-year overall survival (OS) (45.0% vs 5.6%; p = 0.004) than progressive disease. The 2-year OS was significantly higher in the retransplant group ( n = 23) than in the nonretransplant group ( n = 15) (34.8% vs 13.3%; p = 0.034). We analyzed 167 patients who underwent the second allo-HSCT to clarify the impact of pretransplant AZA after the second allo-HSCT. Patients in the AZA group ( n = 21) had significantly higher 2-year disease-free survival (DFS) (32.7% vs 14.5%; p = 0.012) and OS (38.1% vs 17.5%; p = 0.044) than those in the SOC group ( n = 146). Our data demonstrate that AZA is an effective and well-tolerated bridging therapy to the second allo-HSCT.